Learning Cities, Learning Regions, Learning Communities - Norman Longworth (Routledge, 2006)
The development of society depends on our capacity to learn and adapt to new realities and new circumstances. The mark of development in the human story going forth in this millennium depends on the application of creative mind, thought and practice on ancient challenges that find new expression in the pressures of the modern world. The creation of learning societies depends on the fostering of learning cities and they in turn must be made up of learning communities and learning organizations. This book therefore is a timely contribution to an important subject – how do we create learning cities and learning organizations? This work is not an isolated and academic piece. It is a reflection on a European project within which Dublin City was able to play a valuable role. That European project demonstrated the value of different players concerned with the wellbeing of society working together to create a programme which can guide and inform those committed to the ideal of the learning city. We called the programme LILLIPUT. The image is taken from the work of one of Ireland’s great writers, Jonathan Swift. In his work Gulliver’s Travels he uses the image of different lands, one being Lilliput – the land of giants. We can all be giants if we allow the learning imperative to drive our vision and our personal growth